PERAN KEPALA SATUAN KERJA PERANGKAT KOTA (SKPK) DALAM PENCEGAHAN KECURANGAN (FRAUD) (STUDI PENELITIAN PADA SKPK DI KOTA BANDA ACEH) - Pertiwi, Dwi Meutia; Abdullah, Syukriy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research is to determine how the effort and obstacles for heads SKPK in fraud prevention. This research use descriptive qualitative method with primary data and supported by secondary data. The sample was taken by purposive sampling method and the samples are 14 informants. Data collection technique that used in this research is interview and documentation. Data analysis technique that used in this research is data collection, data reduction, data presentation, drawing conclusion/verification. The results of this research is: 1) Heads SKPK in Banda Aceh have been aware about the importance of fraud prevention measures. The efforts of heads SKPK in fraud prevention is to oversee the application of e-performance and e-procurement sustainably, to make innovations of anti-fraud policies, and creating a culture of honesty and high ethics; 2) The obstacles faced by a heads SKPK in fraud prevention such as the density of activity, inhibition, and its psychological burden.